George's secret key to the universe - Hawking, Lucy; Hawking, Stephen (RHCP Digital London, 2014)
Lets you take a ride through the vastness of space and, in the midst of an adventure, discover the mysteries of physics, science and the universe with George, his new friends next door - the scientist Eric and his daughter, Annie - and a super-intelligent computer called Cosmos, which can take them to the edge of a black hole and back again.